Alpha-synuclein in the appendiceal mucosa of neurologically intact subjects - Gray, Madison T.; Munoz, David G.; Gray, Douglas A.; Schlossmacher, Michael G.; Woulfe, John M. (Movement disorders, 2014)
ABSTRACT Parkinson's disease is characterized by the pathological aggregation of Alpha‐synuclein. The dual‐hit hypothesis proposed by Braak implicates the enteric nervous system as an initial site of α‐synuclein aggregation with subsequent spread to the central nervous system. Regional variations in the spatial pattern or levels of α‐synuclein along the enteric nervous system could have implications for identifying sites of onset of this pathogenic cascade. We performed immunohistochemical staining for α‐synuclein on gastrointestinal tissue from patients with no history of neurological disease using the established LB509 antibody and a new clone, MJFR1, characterized for immunohistochemistry here. We demonstrate that the vermiform appendix is particularly enriched in α‐synuclein–containing axonal varicosities, concentrated in its mucosal plexus rather than the classical submucosal and myenteric plexuses. Unexpectedly, intralysosomal accumulations of α‐synuclein were detected within mucosal macrophages of the appendix. The abundance and accumulation of α‐synuclein in the vermiform appendix implicate it as a candidate anatomical locus for the initiation of enteric α‐synuclein aggregation and permits the generation of testable hypotheses for Parkinson's disease pathogenesis. © 2013 International Parkinson and Movement Disorder Society